Karl Dedecius – translator, ambassador of Polish culture in Germany, lonesome humanist - Gonigroszek, Dorota (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
In this article an attempt was made to present the biography of the recently deceased Karl Dedecius – translator, essayist, promoter of Polish-German reconciliation, ambassador of culture and Polish literature in Germany. In the following sections, Dedecius’s life story, his views on the essence of Polish-German relations, the role of language as an opinion-making tool, and literature as an integrative role in culture are outlined. For Dedecius, priorities were to learn about foreign cultures, to interact with other people, to spread tolerance. Biography of Dedecius, a European from Lodz, as mentioned in the article, should be a didactic one.